A novel photomineralization of POME over UV-responsive TiO2 photocatalyst: kinetics of POME degradation and gaseous product formations. Issue 65 (16th July 2015) - Ng, Kim Hoong; Cheng, Chin Kui
<x xml:space="preserve">Abstract</x> Figures (a) settling pond from where the POME was collected, (b) filtered POME was ready for UV-irradiation and (c) POME after 20 h of photocatalytic reaction became clear after the solid TiO2 was removed.